1992
DOI: 10.1002/ijc.2910500614
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen sulphatase activity in hormone‐dependent and hormone‐independent breast‐cancer cells: Modulation by steroidal and non‐steroidal therapeutic agents

Abstract: Oestrogen sulphatase may play an important role in providing intracellular oestrogens from E1S for the growth and maintenance of breast tumours. In this study, we characterized oestrogen sulphatase in the hormone-dependent (ER/PR+) MCF-7 and in the hormone-independent (ER/PR-) MDA-MB-231 breast-cancer cells and, furthermore, examined its modulation by MPA, 4-OH-A4, tamoxifen, danazol, ethinyloestradiol and DHAS in both these cell types. Our detailed study of oestrogen sulphatase activity as a function of incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…It has been observed that both basic fibroblast growth factor and IGF-I increase STS activity in a doseand time-dependent manner in MCF-7 and MDAMB-231 breast cancer cell lines [106]. Moreover, both TNFa and IL-6 up-regulate STS enzyme activity in MCF-7 breast cancer cells.…”
Section: Gene Expression and Regulationmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been observed that both basic fibroblast growth factor and IGF-I increase STS activity in a doseand time-dependent manner in MCF-7 and MDAMB-231 breast cancer cell lines [106]. Moreover, both TNFa and IL-6 up-regulate STS enzyme activity in MCF-7 breast cancer cells.…”
Section: Gene Expression and Regulationmentioning
confidence: 88%
“…Interestingly, STS mRNA levels decreased when MCF-7 breast cancer cells were treated with the progestagen, promegestone (R-5020) [108]. In contrast, it was observed that exposure of MCF-7 and MDA-MB-231 breast cancer cells to the progestagen; medroxyprogesterone acetate, stimulated STS activity in these cells [106].…”
Section: Gene Expression and Regulationmentioning
confidence: 99%
“…Basal STS activity did not differ significantly between HBL-100 and MCF-7 cells in vitro. While we are to our knowledge the first to study STS activity in non-malignant human breast cells (basal and after treatment), basal STS activity in MCF-7 cells has been measured before [25,35,37,[38][39][40][41][42][43][44][45][46][47] revealing varying results which might be due to different assay protocols. For example, some authors used intact cells [25,37,38,[42][43][44][45][46][47][48][49][50][51], others cell homogenates [39,50].…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary study the effect of danazol therapy (800 mg/day for 2 weeks) on the conversion ratio (CR) of oestrone sulphate to oestrone was investigated in three menopausal women with breast cancer (Purohit et al 1992). For two of the three women, a 40% decrease in the CR was detected, while no change occurred in the third subject.…”
mentioning
confidence: 99%
“…In intact MCF-7 breast cancer cells, using a physio¬ logical substrate concentration (2 nM), danazol (10 µ ) inhibited sulphatase activity by 62% (Purohit & Reed 1992 Santner & Santen (1993), such an effect is likely to be secondary to their ability to bind to the ER and block the action of oestradiol.…”
mentioning
confidence: 99%